Cash Flow Management and Earnings Sustainability in Member-Based Financial Institutions: Evidence from Indonesia - Ni Wayan Novi Budiasni; Ni Luh Putri Aryani; Muhammad Luthfi Hamzah; Tilovmurodov Dostonbek Furqat Ugli (INVEST : Jurnal Inovasi Bisnis dan Akuntansi, 2025)
This study analyzes cash flows and earnings quality at KSP Karya Abadi in Pemaron Village over 2021–2023. The research uses a descriptive quantitative method with a financial statement approach, focusing on income statements and cash flow reports. The results show that although net income fluctuated—decreasing in 2022 and rising significantly in 2023—the efficiency of earnings, as measured by the Net Profit Margin (NPM), declined from 62.8% in 2021 to 57.1% in 2022 and remained stagnant in 2023. Operating cash flows remained positive throughout the three years, reflecting the cooperative’s ability to generate cash from its core business activities. Earnings quality, assessed by comparing operating cash flows to net income, was categorized as very good in 2021 and 2022, and moderately good in 2023. These findings emphasize the importance of evaluating the nominal value of earnings and their quality and sustainability over time.